UJI KARAKTERISTIK SEDIAAN SALEP EKSTRAK ETANOL BUAH MAKASAR (Brucea javanica [L.] Merr) SEBAGAI KANDIDAT SALEP UNTUK LUKA INCISI DAN LUKA DIABETES - Jacob, Jois Moriani; Oematan, Aven B.; Maakh, Yorida Febry (JURNAL KAJIAN VETERINER, 2022)
Makasar fruit (Brucea javanica [L]. Merr) has been widely used as herbal medicine to treat various types of diseases through simple processing. However, the use of Makasar fruit drugs with topical application as an ointment to treat incision wounds or diabetic wounds is extremely rare. The purpose of this research is to produce ointment and to assess the physical quality of the ointment made from the ethanolic extract of the Makassar fruit. The ointment used in this study was made with ethanol extract of Makassar fruit, alpha tocopherol, propyl-paraben, and Vaseline album. The data were observed descriptively and using a qualitative method. This study used two ointment concentrations, 15% and 20%, which were tested three times for each physical evaluation (organoleptic test, homogeneity test, dispersibility test, and pH test). The results showed that the ethanol extract of Makassar fruit could be formulated as an ointment, and the physical evaluation of the ointment discovered that the ointment met the organoleptic standards and the homogeneity standards. Furthermore, the pH test revealed that the ointment was safe to use; however, only 1 sample (repeat 1 concentration of 20%) confirmed that it did not meet the pH requirements because it was lower than the standard (acid pH). Furthermore, the dispersion tests indicated that the ointment did not meet the ointments dispersion standard. Conclusion: because the physical examination showed that the ointment met the standard values, the ointment can be made from the ethanol extract of Makassar fruit. However, because the ointment's spreadability is below the standard value, it must be taken into account.